(untitled) (World Science, 2019)
Relation to religion and religious values in the poetry of Suhrab Sipehri, occupies a special place among the spiritual values of the poet. Being an inextricable part of Sipehri’s worldview, this attitude can be called the main idea of his creative heritage, which acts as a kind of harmony between the poet’s society, being and “I”. In particular, the concept of the essence of religion and being as the main means of expression is manifested to a greater or lesser extent in almost all verses of Suhrab Sipehri. According to Sipehri, religion and faith are a spiritual tool that can satisfy a person’s moral needs. It cannot be imposed or imposed on anyone by force. Faith should not come from outside, but from the person himself, from his moral and spiritual needs, otherwise it will not turn into a means of improving a person, or ennoblement of him, but as a means restricting human freedom.